PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP PENGAMBILAN KEPUTUSAN KONSUMEN DALAM MEMILIH SEKOLAH DI SD ISLAM AS-SHOFA - Nur Hijjah Isriana; Rina Selva Johan; RM Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research aims to determine the effect of servicequality and propmotion to the decision making at SD Islam As-Shofaa Pekanbaru partially and simultaneously, with a sample size of 60 people. The sampling technique using purposive sampling method, that taking sample by using specific criteria. Data analysis methods use of multiple linear regression. Based on the results obtained F-value (30,911)> F-table (2; 57) = 2.47 means simultaneously servicequality and promotion have a positive and significant impact on the decision making at SD Islam As-Shofaa Pekanbaru. The results of the partial test for service quality variable t-value (2.170)> t-table (1.67) means servicequality influence on decision making. Pormotion variables with the t-value (4.595)> t- table (1.67) means that the promotion has a significant effect on the decision making at SD Islam As-Shofaa Pekanbaru. The coefficient of determination obtained amounted to 0.520 it showed that 52% change in the decision making at SD Islam As-Shofaa Pekanbaru determined by the independent variable which is the service quality and promotion, while 48% is determined by other factors.Keyword: Service Quality, Promotion, Decision Making